2023
DOI: 10.22541/essoar.169008309.90443492/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical role of vertical radiative cooling contrast in triggering episodic deluges in small-domain hothouse climates

Abstract: Seeley and Wordsworth (2021) showed that in small-domain cloud-resolving simulations the pattern of precipitation transforms in extremely hot climates (≥320 K) from quasi-steady to organized episodic deluges, with outbursts of heavy rain alternating with several dry days. They proposed a mechanism for this transition involving increased water vapor absorption of solar radiation leading to net lower-tropospheric radiative heating. This heating inhibits lower-tropospheric convection and decouples the boundary la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Figure 3 also highlights that, under the Maritime Continent vertical profile, an increase in SST correlates with a reduction in the frequency of rain events and an increase in their characteristic magnitude. A recent study has shown that the period of the episodic deluges can be predicted by considering the time for radiation and reevaporation to cool the lower atmosphere (Song et al, 2023), a factor expected to vary with SST. Furthermore, it has been demonstrated that, even under the same RHR vertical profile, higher SST facilitates a smoother transition into the episodic deluge regime (Dagan et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 also highlights that, under the Maritime Continent vertical profile, an increase in SST correlates with a reduction in the frequency of rain events and an increase in their characteristic magnitude. A recent study has shown that the period of the episodic deluges can be predicted by considering the time for radiation and reevaporation to cool the lower atmosphere (Song et al, 2023), a factor expected to vary with SST. Furthermore, it has been demonstrated that, even under the same RHR vertical profile, higher SST facilitates a smoother transition into the episodic deluge regime (Dagan et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…In a seemingly unrelated context to absorbing aerosols, recent research has demonstrated that under hothouse climate conditions-warmer than our current climate, believed to have existed in the distant history of our planet -precipitation shifts from the quasi-equilibrium condition observed today to an "episodic deluge" regime. This regime is characterized by short and intense outbursts of rainfall separated by multi-day dry spells (Dagan et al, 2023;Seeley & Wordsworth, 2021;Song et al, 2023;Spaulding-Astudillo & Mitchell, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloud-resolving model SAM is publicly available at M. Khairoutdinov (2004). The data in this study is publicly available at Song et al (2023).…”
Section: Appendix A: Experiments Results With Discontinuous Heating R...mentioning
confidence: 99%